Effects of the type of recovery training on the concentric strength of the knee extensors - Amiridis, I. G.; Cometti, G.; Morlon, B.; Martin, L.; Martin, A. (Journal of Sports Sciences, 1997)
The aim of this study was to examine the effects of specific concentric and eccentric training on concentric muscular strength following an initial standardized period of excessive training that combined concentric and eccentric actions. For a period of 12 weeks, 37 young elite female basketball players performed standardized training, which included concentric and eccentric actions at 70% and 110% of one-repetition maximum (1-RM), respectively. They were then divided into three groups that followed 12 week programmes which included concentric (C-E/C, n = 13), eccentric (C-E/E, n = 13) or a combination of both concentric and eccentric (C-E/C-E, n = 11) exercises. The standardized and specific training programmes consisted of 16 and 8 sets of eight repetitions respectively, performed four times a week. Eleven players who did not participate in either the standardized or specific training programmes served as controls (n = 11). Following the initial 12 weeks of standardized training, the concentric strength of the knee extensors was evaluated isokinetically and using leg-press and squat-jump tests. Significant (P < 0.05) reductions in isokinetic torque, and leg-press and squat-jump performance, were seen. The C-E/C group showed significant (P < 0.05) increases in isokinetic torque, and leg-press and squat-jump performance, after 24 weeks of training when compared with pre-training values. Conversely, no significant differences were noted for the C-E/E and C-E/C-E groups. These findings confirm the mode specificity principle, as only the concentric specific training programme improved the concentricstrength of the knee extensors.